2013
DOI: 10.1016/j.paid.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of psychopathy-related traits in predicting impersonal sex and hostile masculinity

Abstract: This paper reports the relative contributions of several facets of subclinical psychopathy (i.e., callous affect, erratic lifestyle, interpersonal manipulation), subclinical narcissism (i.e., entitlement, exploitation), and trait aggression (i.e., anger) to the prediction of four enduring attitudes towards women and sexual assault (i.e., hostility towards women, negative attitudes regarding women, sexual dominance, impersonal sex) and a behavioral indicator of an impersonal sexual behavior (i.e., number of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Although some link coercive control to patriarchy [86], case histories of perpetrators suggest psychopathy [86,90] and women perpetrate coercive control [87,88]. It is likely that psychopathic personality traits associated with Factor 1 predispose to coercive control and also increase susceptibility to messages regarding patriarchy [91].…”
Section: Is Psychopathy Associated With Partner Abuse?mentioning
confidence: 99%
“…Although some link coercive control to patriarchy [86], case histories of perpetrators suggest psychopathy [86,90] and women perpetrate coercive control [87,88]. It is likely that psychopathic personality traits associated with Factor 1 predispose to coercive control and also increase susceptibility to messages regarding patriarchy [91].…”
Section: Is Psychopathy Associated With Partner Abuse?mentioning
confidence: 99%
“…That is why psychopathy has been widely explored in forensic contexts, mostly in order to predict criminal recidivism (Salekin, 2008) or the type of a criminal act (Porter, ten Brinke, & Wilson, 2009). However, it is shown that psychopathy is useful for the explanation of various behaviors, including the ones outside forensic contexts, like workplace behavior (Mathieu & Babiak, 2015), social interactions in friendships (Jonason & Schmitt, 2012) or romantic partner relations (LeBreton, Baysinger, Abbey, & Jacques-Tiura, 2013).…”
Section: Psychopathy and Its Operationalizationsmentioning
confidence: 99%
“…Certain characteristics of sexual aggressors, such as deficiencies in cognitive planning and increased impulsivity (Carvalho & Nobre, 2012; Bernat, Calhoun, & Adams, 1999; LeBreton, Baysinger, & Abbey, 2013) and holding callous sexual beliefs (Abbey & Jacques-Tiura, 2011; Baumeister et al, 2002; LeBreton, Baysinger, & Abbey, 2013), are relatively well-documented, while the potential contribution of affect in the decision to engage in sexual aggression is less understood. Subclinical levels of psychopathic traits have been linked to what has been termed “calloused attitudes” towards women and endorsement of rape myths, suggesting that these characteristics may be common in a subset of individuals who engage in sexual coercion (Baumeister et al, 2002; Lalumière & Quinsey, 1996; LeBreton, Baysinger, & Abbey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical levels of psychopathic traits have been linked to what has been termed “calloused attitudes” towards women and endorsement of rape myths, suggesting that these characteristics may be common in a subset of individuals who engage in sexual coercion (Baumeister et al, 2002; Lalumière & Quinsey, 1996; LeBreton, Baysinger, & Abbey, 2013). Psychopathic traits, such as emotional under-reactivity and lack of remorse for one’s actions, have been found to be related to physiological under-reactivity as measured by electrodermal activity (EDA; see Fowles, 2000 for review) and salivary cortisol (O’Leary et al, 2007).…”
Section: Introductionmentioning
confidence: 99%